Gesturing makes learning last - Cook, Susan Wagner (2007)
The gestures children spontaneously produce when explaining a task predict whether they will subsequently learn that task. Why? Gesture might simply reflect a child’s readiness to learn a particular task. Alternatively, gesture might itself play a role in learning the task. To investigate these alternatives, we experimentally manipulated children’s gesture during instruction in a new mathematical concept. We found that requiring children to gesture while learning the new concept helped them retain the knowledge they had gained during instruction. In contrast, requiring children to speak, but not gesture, while learning the concept had no effect on solidifying learning. Gesturing can thus play a causal role in learning, perhaps by giving learners an alternative, embodied way of representing new ideas. We may be able to improve children’s learning just by encouraging them to move their hands.